PENGEMBANGAN APLIKASI SIAPIK UNTUK MEMPERMUDAH PENCATATAN KEUANGAN PADA UMKM DI DESA WUKIRSARI - Joy Geral Djami Raga; Rochmad Bayu Utomo (LPPI UMN AL WASHLIYAH, 2025)
Financial record management for MSMEs in Wukirsari Village still faces challenges such as manual recording, lack of accounting knowledge, and limited time. This study aims to improve MSME capabilities in systematic financial recording using the digital SIAPIK application through a participatory approach. The implementation method includes socialization, account creation and transaction recording practice, independent exercises, and joint evaluation. Results show enhanced mastery of SIAPIK application use and accurate, complete financial report preparation. The conclusion states that digital assistance and training effectively support better financial management and sustainable MSME business development in the village. Continued mentoring with strengthened digital literacy and accounting is recommended.